2018
DOI: 10.1029/2017rg000584
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of the Heat Pulse Method for Soil Physical Measurements

Abstract: Accurate and continuous measurements of soil thermal and hydraulic propertiesare required for environmental, Earth and planetary science, and engineering applications, but they are not practicallyobtained by steady-state methods. The heat pulse (HP) method is a transient method for determinationof soil thermal properties and a wide range of other physical properties in laboratory and field conditions. The HP method is based on the line-heat source solution of the radial heat flow equation. This literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 124 publications
(64 citation statements)
references
References 298 publications
(742 reference statements)
1
57
0
6
Order By: Relevance
“…The LY2018 model was developed based on the basic series-parallel model using a small dataset (28 measurements) of Aeolian sands from the Tibetan Plateau [21]. The RH2018 model (Figure 1(6)) is in fact the modified form of HS2012 (Figure 1(4)) model by multiplying an F factor based on Equation (12). However, it should be noted that Equation (12a) gave an unreasonably high value at S r < 0.1 and only Equation (12b) was used for all degrees of saturation in this study.…”
Section: Analytical or Mixing Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LY2018 model was developed based on the basic series-parallel model using a small dataset (28 measurements) of Aeolian sands from the Tibetan Plateau [21]. The RH2018 model (Figure 1(6)) is in fact the modified form of HS2012 (Figure 1(4)) model by multiplying an F factor based on Equation (12). However, it should be noted that Equation (12a) gave an unreasonably high value at S r < 0.1 and only Equation (12b) was used for all degrees of saturation in this study.…”
Section: Analytical or Mixing Modelsmentioning
confidence: 99%
“…The AA2016 model (Figure 3(4)) generally overestimated the measured λ eff as a whole, which may be attributed to the fact that AA2016 was developed based on steady-state measurements (i.e., guarded hot plates). Steady-state measurements are prone to water redistribution in unsaturated soils, which changes the thermal conductivity being measured [12,62]. This may explain why Alrtimi et al [17] found that the models of de Vries [63], Johansen [39], Côté and Konrad [41], Lu et al [48], Chen [15] and Haigh [16] could not be used to properly predict thermal conductivity of Tripoli sand measured with the steady-state measurements.…”
Section: Linear or Non-linear Regression Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al (2015) reported that its voltage signals during and shortly after selfcalibration should be discarded from data analysis as the self-heating could bias the voltage signals. The threeneedle heat-pulse sensor (Ren et al 1999) has the ability to measured l s in situ and is a good candidate to obtain independent soil heat flux using the gradient method (Cobos and Baker 2003;Ochsner et al 2006;Heitman et al 2008a,b;Xiao et al 2011;Peng et al 2015;Lu et al 2016;He et al 2018).…”
Section: E G P Improvements After Correcting For Heat Flow Divergencementioning
confidence: 99%
“…In each of them, five plants per species were grown in the split-root setup for four months until the roots reached the growth mix in the lower tube segment. The soil volumetric water content was monitored with the time domain reflectometry (TDR) technique [23]. A three-rod (1.5 mm in diameter, 15 cm long) TDR stainless steel probe was vertically inserted into the upper tube.…”
Section: Experimental Design and Deuterium (D)-enriched Water Treatmentsmentioning
confidence: 99%